2022
DOI: 10.1111/jocn.16245
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ perceived barriers to the delivery of person‐centred care to complex patients: A qualitative study using theoretical domains framework

Abstract: Aims and Objectives To determine nurses’ perceived barriers to the delivery of person‐centred care to complex patients with multiple chronic conditions in acute care settings. Background Complex patients have multiple physical and mental health problems, and their life is also greatly affected by sociocultural and economic determinants of health. These patients require person‐centred care, but nurses often find it challenging to provide effective care to these patients due to their complex health needs. Design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…Rankings of implementation strategies were denoted as confirmed if the relevance was supported by the qualitative findings and the Q‐sort survey results. If quantitative results were inconsistent with the qualitative or vice versa, the ranking/finding was discordant (Younas, Inayat, et al, 2022; Younas, Pedersen, et al, 2022).…”
Section: Integration Of Qualitative Findings and Q‐sort Survey Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rankings of implementation strategies were denoted as confirmed if the relevance was supported by the qualitative findings and the Q‐sort survey results. If quantitative results were inconsistent with the qualitative or vice versa, the ranking/finding was discordant (Younas, Inayat, et al, 2022; Younas, Pedersen, et al, 2022).…”
Section: Integration Of Qualitative Findings and Q‐sort Survey Resultsmentioning
confidence: 99%
“…Previous research also demonstrated that addressing nurse burnout and distress is critical for the provision of compassionate care (Babaei & Taleghani, 2019; Valizadeh et al, 2016). This brings to attention the interplay of personal, interpersonal, and organizational factors that affect nurses' capability to provide compassionate care for marginalized patient populations (Tehranineshat et al, 2019; Younas, Inayat, et al, 2022; Younas, Pedersen, et al, 2022), indicating that greater efforts are required at the organizational level to support nurses in their compassionate care efforts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings bring to attention the importance of self-awareness among nurses when they are caring for complex patients. Nurses must be reminded of the social determinants of health influencing healing and recovery (Porr, 2017), which will enhance their sensitivity to the multifaceted health and social care needs of complex patients (Younas et al, 2022). Nurses must be keenly aware of how pejorative attitudes can hinder the provision of compassionate nursing care for complex patients.…”
Section: Awareness and Compassionate Carementioning
confidence: 99%
“…The health and illness of individuals with complex needs situates within broader sociocultural and economic environments. Increasingly recognised are the sociocultural determinants (e.g., poverty, education level, and access to resources) that can affect the ability of individuals with complex needs to manage their chronic conditions which may result in further deterioration of symptoms (Manning & Gagnon, 2017; Younas et al, 2022). Many individuals with complex needs experience homelessness, poverty, and are susceptible to drug and medication addictions (Arnold et al, 2020).…”
mentioning
confidence: 99%